Pemberdayaan Masyarakat dalam Mengendalikan Tekanan Darah di Posbindu Delima, Sawangan Depok: Community Empowerment in Controlling Blood Pressure at Posbindu Delima, Sawangan Depok - Bustamam, Nurfitri; Hardini, Niniek; Fauziah, Cut (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
In 2023, data from Posbindu Delima, Sawangan Depok, showed that 37 residents had blood pressure ≥140/90 mmHg (hypertension), and 5 residents had already experienced complications from hypertension, such as stroke and heart disease. In response to this issue, a community service was conducted to help control the blood pressure of residents with hypertension by adopting a healthy lifestyle. The community service consists of three stages: disseminating guidelines for filling out the healthy lifestyle logbook and socializing the community service program, providing direct education and education using WhatsApp, and evaluating. The knowledge level, medication adherence, and health of residents with hypertension were measured before and after community service. The evaluation of healthy lifestyle implementation was based on logbook data. The 5-week community service was attended by 12 residents, most of whom (66.7%) were female with an average age of 60.6 ± 8.6 years. The community service results showed the knowledge level of residents increased significantly, but there was no statistical difference in medication adherence. After adopting a healthy lifestyle, there were significant health improvements, including increased residents with controlled blood pressure, weight loss, and reduced waist circumference. It can be inferred that the community service successfully increased knowledge and encouraged residents with hypertension to adopt a healthy lifestyle, resulting in controlled blood pressure.